Pd-Catalyzed double N-arylation of primary amines to synthesize phenoxazines and phenothiazines. Issue 30 (17th July 2017) - Zhang, Lu; Huang, Xin; Zhen, Shan; Zhao, Jing; Li, Heng; Yuan, Bingxin; Yang, Guanyu
Abstract : Pd-Catalyzed tandem N -arylation of primary amines with aryl halides to synthesize phenoxazine and phenothiazine derivatives. Abstract : An efficient and versatile Pd-catalyzed tandem C–N bond formation between aryl halides and primary amines is developed. The transformation allows a one-pot synthesis of phenoxazine and phenothiazine derivatives with a broad range of substitution patterns from readily available precursors.